Gender differences in HIV knowledge among adolescents and young people in low-and middle-income countries: a systematic review - Chory, Ashley; Gillette, Emma; Callen, Grant; Wachira, Juddy; Sam-Agudu, Nadia A.; Bond, Keosha; Vreeman, Rachel (Frontiers in Reproductive Health, 2023)
Objectives This review seeks to critically analyze studies assessing gender differences in HIV-related knowledge among adolescents and young people in low- and middle-income countries. Methods Using PRISMA guidelines and searching Pubmed and Scopus online databases, the search strategy combined search keywords with Boolean operators: (HIV OR AIDS) AND (knowledge) AND (gender) AND (adolescents). AC and EG conducted the search and independently reviewed all articles in Covidence software; conflicts were resolved by GC. Articles were included if they evaluated differences in HIV knowledge in at least two groups ages 10–24 and were implemented in a low or middle-income country. Results The search resulted in 4,901 articles, of which fifteen studies, implemented in 15 countries, met selection criteria. Twelve evaluated differences in HIV knowledge in school settings; three evaluated participants in clinic settings. Adolescent males consistently scored higher in composite knowledge scores, as well as knowledge of HIV transmission, prevention, attitudes and sexual decision-making. Conclusion We found gender-based discrepancies between knowledge, perception of risk and HIV prevalence among youth globally, with boys consistently scoring higher in HIV knowledge. However, there is significant evidence that social and cultural contexts render girls at high risk of HIV infection, and the gaps in girls' knowledge and boys' roles in HIV risk must be addressed urgently. Future research should consider interventions that facilitate discussion and HIV knowledge building across genders.